The French implementation study PARENTHESE to improve prenatal care of immigrant women. (30th September 2020) - Azria, E; Eboue, F; Fallon, M; Khomry, O; Sauvegrain, P; Vasseur, P; Akrich, M; Joinau, F
Abstract: Numerous studies have shown that non-Western immigrant women have higher maternal and perinatal mortality and morbidity than women and children from host countries. This increased risk is partly explained by less access to quality antenatal care and more sub-optimal care. The organisation and provision of prenatal care in France remain unchanged on a model that is not very sensitive and adaptable to the specific needs of certain groups such as non-Western migrant women. Group prenatal care, an alternative and innovative model, can theoretically be rigorously implemented within the framework of the recommendations for prenatal care set by the French Haute Autorité de Santé and thus meet the objectives assigned to it. This alternative method of monitoring, implemented in different US settings, seems to increase access and adherence to prenatal monitoring, as well as women's involvement in its monitoring. Some studies also suggest that this type of prenatal monitoring could also reduce maternal and perinatal risk. Such intervention has never been tested in France and moving away from a prenatal monitoring model based on individual monitoring towards a group model requires overcoming significant cultural barriers. Before being able to test the impact of a complex intervention such as group prenatal care for migrant women and wider deployment, we set up a pilot study with the aim of precisely defining the intervention and preparing and documenting its implementation process in three different sites using qualitative and quantitative approaches. It is also to evaluate its acceptability for women who participate in these groups as well as for professionals. In addition to presenting this pilot study at this workshop, the objective of this presentation is also to highlight the importance of contextual considerations in the design of the intervention or its implementation in the particular context of intervention aimed at improving migrant populations' health.